Pharmacogenomic Biomarker Information in FDA‐approved Paediatric Drug Labels. (21st November 2014) - Kim, Therasa; Han, Nayoung; Sohn, Minji; Oh, Jung Mi; Lee, Eui‐Kyung; Ji, Eunhee; Kim, In‐Wha
Abstract Gene maturation differs between paediatric and adult populations, and the extrapolation of adult pharmacogenomic information to paediatrics is not always appropriate. We sought to determine the extent of paediatric pharmacogenomic trial translation into US FDA‐approved labels and to evaluate needs for biomarker studies. Using FDA's Table of Genomic Biomarkers and Drugs@FDA website, 38 pharmacogenomic biomarkers in 56 drug labels were identified with possible application in paediatrics. Of these 56 drugs, biomarker comparison against 'Very Important Pharmacogenes (VIPs)' defined in PharmGKB's database revealed a total of eight VIPs labelled among 41 drugs. One hundred and thirty‐nine product reviews posted on the FDA website under the Best Pharmaceuticals for Children Act and Paediatric Research Equity Act between October 2007 and July 2014 were examined. Review screening identified 43 drugs with 'pharmacogenomic' content, of which only three were true genotyping study reviews for proton pump inhibitors, all evaluating CYP2C19 polymorphisms. Pantoprazole was the sole drug labelled with pharmacogenomic information obtained specifically from paediatric trials. Clinicaltrials.gov was searched to further evaluate the current availability of pharmacogenomic studies in the paediatric population. Of the 33, 132 trials registered on Clinicaltrials.gov, 137 were labelled as paediatric pharmacogenetic and pharmacogenomic studies. Pharmacogenomic studies directly conducted in paediatric patients are lacking, and thus, pharmacogenomic biomarker information based on adult studies is commonly presented in FDA‐approved labels for use in paediatric patients. Considering differences in gene expression and physiological maturation between paediatric and adult populations, studies investigating pharmacogenomic effects specifically in paediatric patients should be conducted whenever significant biomarkers are available.